Pengaruh Bauran Pemasaran Terhadap Kepuasan Dan Loyalitas Pasien Rawat Inap Di Rumah Sakit Umum Daerah Dr Soediran Mangun Sumarso Kabupaten Wonogiri - Rejeki, Sri (-)
This study aims are to determine the effect of the marketing mix to the satisfaction and loyalty of inpatients in the General Hospital of Dr Soediran Mangun Sumarso Wonogiri. This study is a survey research. The data are primary data by sampling sample in this study were 100 employees at the General Hospital of Dr Soediran Mangun Sumarso Wonogiri. Sampling techniques in this study using census data in this research will be obtained directly from the results of questionnaires. The analytical tool used Instrument Research Test, ing linearity Test, path analysis and regression with t test, F test and R2 test. T test results showed the price has a significant effect in patient satisfaction. Process has not a significant effect on patient satisfaction. Personal has not a significant effect in patient satisfaction. Physical has significantly influence patient satisfaction. Price has significant effect on loyalty. Process has a significant effect on loyalty. Personal has a significant effect on loyalty. Physical has a significant effect on loyalty. Patient satisfaction has significantly influence loyalty. Test results simultaneously (Test F) concluded simultaneously variables price, process, personal and patient satisfaction are significant positive effect on loyalty. R2 total is 98.5%. This means that the loyalty of inpatients is explained by the price, process, personal, physical and patient satisfaction amounted to 98.5% and the remaining 1.5% described by other variables outside the model, Indirect effect of physical loyalty through an intervening variable patient satisfaction is the most effective path to increase loyalty, as positive, the most influential and significant.Keywords: price, process, personal satisfaction and loyalty.